Digital Marketing of Batik Enterprises in Serasi Batik Community, Sutorejo Village, Surabaya City, Indonesia - Mujanah, Siti; Halik, Abdul; Nisak Achmad, Nursaadaatun; Zuono, Trida Trisno; Bin Azam, Yusof Saqafi (Portal ABDIMAS, 2024)
This Community Service activity was carried out with the aim of providing skills to the Batik Serasi MSME group in Sutorejo Village Mulyorejo Surabaya City about Digital marketing strategies so that they can market their products online so that they can expand their market network. The method used in this community service is to provide assistance and training in making online marketing applications as one of the batik marketing strategies in order to brand and sell batik products. The results obtained in this activity are that Batik Serasi MSMEs have the skills to make online marketing applications as one of the marketing strategies, namely by creating Instagram and Facebook accounts to market Batik Serasi, besides that they are also skilled in creating content, so that they can promote their products on social media and marketplaces so that they can sell Batik products. Business management skills are also provided so that Batik MSMEs who join Batik Serasi can manage their businesses appropriately able to plan, organize and control the business and provide financial bookkeeping skills so that MSMEs will know how much profit is obtained from the results of their business, thus it is expected that they can improve the welfare of all members of Batik Serasi, Sutorejo, Surabaya Indonesia.